Recent community warming of moths in Finland is driven by extinction in the north and colonisation in the south - Emilie E. Ellis; Laura H. Antão; Andréa Davrinche; Jussi Mäkinen; Mark Rees; Irene Conenna; Ida-Maria Huikkonen; Reima Leinonen; Juha Pöyry; Anna Suuronen; Anna-Liisa Laine; Marjo Saastamoinen; et al. (Nature Communications)
Abstract As the climate warms, species are shifting their ranges to match their climatic niches, leading to the warming of ecological communities (thermophilisation). We currently have little understanding of the population-level processes driving this community-level warming, particularly at rapidly warming high latitudes. Using 30 years of high-resolution moth monitoring data across a 1200 km latitudinal gradient in Finland, we find that higher latitude communities are experiencing more rapid thermophilisation. We attribute this spatial variation to colonisation-extinction dynamics, both for the full community and for thermal affinity groups. Our findings reveal that latitudinal variation in the pathways underpinning thermophilisation is the net outcome of opposite forces: in the north, community warming is driven by the extinction of cold-affiliated species, while in the south it is driven by high colonisation rates of warm-affiliated species. Thus, we show how species’ thermal affinities influence community reorganisation and highlight the elevated extinction risk among cold-affiliated species.